Safety, immunogenicity and immune-persistence of a lyophilized human rabies vaccine (Vero cells) under Zagreb and Essen regimens: a randomized, open-label, controlled phase III clinical trial in healthy participants aged 10–60 years in China - Liang, Zhenzhen; Chen, Xu; Xing, Bo; Hu, Xiaosong; Liu, Miaomiao; Zhang, Xinpei; Shen, Yugang; Wang, Yan; Chen, Yingping; Lv, Huakun; Mao, Yu (Frontiers in Immunology, 2024)
BackgroundRabies continues to be a significant global public health concern, particularly in the Asia region where it is associated with high mortality rate. The administration of effective vaccination is essential in preventing this potentially fatal viral infection. The objective of this study was to evaluate the immunogenicity and safety of two rabies vaccination schedules: the Zagreb (2–1–1) and Essen (1–1–1–1–1) regimens, in a cohort of healthy Chinese individuals aged 10-60 years.MethodsWe conducted a randomized, open-label, controlled, non-inferiority phase 3 trial from July 2021 to November 2022, enrolling a total of 1200 participants. Participants were randomly assigned to receive either the Zagreb or Essen vaccination regimen. The primary outcomes were safety, immunogenicity, and immune persistence. Safety was monitored through adverse event reporting, while immunogenicity was determined by measuring rabies-virus-neutralizing antibody (RVNA) concentrations using the rapid fluorescent focus inhibition test (RFFIT). Immune persistence was evaluated at 3, 6, and 12 months post-vaccination.ResultsThe two vaccination regimens exhibited comparable safety records, with mild and transient adverse events predominantly occurring within 0-3 days post-vaccination. The Zagreb regimen demonstrated non-inferiority in terms of seroconversion rates and geometric mean concentrations (GMCs) of antibodies compared to the Essen regimen at both 14 days post-first vaccination and 14 days post-full vaccination. Additionally, both groups displayed nearly 100% seropositivity rate at 3,6, and 12 months. No serious adverse events associated with vaccination were reported.ConclusionThe findings of this Phase 3 clinical trial provide compelling evidence that the Zagreb regimen is a feasible alternative when compared to the Essen regimen for rabies vaccination, offering a more pragmatic and cost-efficient approach to rabies prevention and control.Clinical trial registrationhttp://www.chinadrugtrials.org.cn, identifier CTR20210426.